A review of Palaearctic Teuchophorus, with a new species from Bulgaria (Diptera: Dolichopodidae) - Pollet, Marc A.a.; Kechev, Mihail (Zootaxa, 2007)
The Palaearctic species of Teuchophorus are reviewed and a key provided to males. T. chaetifemoratus is described as new from Bulgaria. The male of this species is easily recognized by the ventral and posteroventral rows of strong curved bristles on the hind femur and, in contrast to all other Palaearctic species, its hind tibia does not show any peculiar chaetotaxy. It shares the same habitat preference as most of its Western European congeners, whereas Mediterranean species occur in more open habitats. T. simplex Mik is recorded for the first time from Bulgaria. T. bisetus Loew is reinstated as a distinct species, whereas T. tenuemarginatus Strobl most probably does not belong to Teuchophorus and is regarded as nomen dubium. In contrast to the literature, European, African and some Oriental Teuchophorus species have 6 dorsocentral bristles instead of 5, and the entire generic range encompasses 4 to 6 dorsocentral bristles. Two morphological features are found in both sexes of all Teuchophorus species and are the only reliable characters to separate this genus from Sympycnus (sensu lato): the oblique position of crossvein dm-cu and the anterior bend at the base of the distal section of vein M 1 .